Pelatihan Model Contextual Teaching and Learning (CTL) Berbantuan Media Interaktif Pada Pembelajaran IPAS SD - Kembar Habibi, Roy; Fitri Istiawati, Novia; Pangestu, Deviyanti; Nuraini, Siti; Ayuningsih, Silva (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2026)
The learning process of Integrated Science and Social Studies (IPAS) in elementary schools still faced several challenges, such as monotonous learning activities, the suboptimal use of active learning models, and the limited use of interactive learning media. These conditions affected students’ motivation and learning outcomes. Therefore, this training program aimed to improve teachers’ understanding and skills in implementing the Contextual Teaching and Learning (CTL) model assisted by interactive media in IPAS learning at the elementary school level. The activity was conducted in Pesawaran Regency and involved principals, teachers, researchers, and students. The method used a participatory and educational approach based on digital technology, which included educational webinars, CTL implementation training, workshops on developing interactive media, teaching practice mentoring, the establishment of a learning community, and activity evaluation. The results showed an improvement in teachers’ understanding and skills in designing and implementing IPAS learning so that it became more contextual and interactive. In addition, the program produced learning tools that could be used in the teaching and learning process. Thus, the training on the Contextual Teaching and Learning model assisted by interactive media was able to improve the quality of IPAS learning through increased student motivation and learning outcomes in elementary schools.